Electrolyte for nickel-zinc battery and nickel-zinc battery thereof

By using electrolyte additives of borate, fluorine and chloride salts in nickel-zinc batteries, a stable interface film is formed, which solves the problems of hydrogen evolution reaction and zinc corrosion, and improves the cycle life and high temperature stability of the battery.

CN120261736APending Publication Date: 2025-07-04SHENZHEN HIGHPOWER TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510202998.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-24
Publication Date
2025-07-04

AI Technical Summary

Technical Problem

Nickel-zinc batteries have problems such as reducing battery high temperature stability and reduced cycle life due to hydrogen evolution reaction and zinc corrosion.

Method used

Using electrolyte additives containing borate, fluorine and chloride salts, a barrier structure is formed at the interface of the negative electrode of zinc, and synergistically controls zinc ion deposition and corrosion, and inhibits hydrogen evolution reaction and zinc corrosion.

Benefits of technology

It extends the cycle life of the battery and improves the high-temperature and safety performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

Aiming at the problems that the high-temperature stability of an existing nickel-zinc battery is reduced and the cycle life of the battery is shortened due to hydrogen evolution reaction or zinc corrosion, the invention provides the electrolyte for the nickel-zinc battery and the nickel-zinc battery thereof. The electrolyte for the nickel-zinc battery comprises a first additive and a second additive, the first additive comprises borate, and the second additive comprises one or two of villiaumite and chlorine salt. According to the electrolyte for the nickel-zinc battery provided by the invention, the first additive can form a barrier structure on a zinc negative electrode interface, and the first additive and the second additive are synergistic, so that the stability of the zinc negative electrode interface can be enhanced, a stable interface film is formed on the negative electrode interface, and side reactions such as hydrogen evolution reaction or zinc corrosion are inhibited; therefore, the cycle life of the battery is prolonged, and the high-temperature performance and the safety performance of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of nickel-zinc batteries, and particularly to an electrolyte for nickel-zinc batteries and a nickel-zinc battery using the same. Background Art

[0002] Nickel-zinc batteries belong to alkaline secondary batteries, and their operation is based on redox reactions. During the charging process, the nickel electrode at the positive electrode undergoes a reduction reaction, and the high-valent nickel oxide accepts electrons and is reduced to a low-valent substance; at the negative electrode of zinc, an oxidation reaction occurs, where metallic zinc loses electrons to become zinc ions, dissolves into the electrolyte, and migrates towards the positive electrode under the action of an electric field. During discharge, the reaction proceeds in the reverse direction, zinc ions gain electrons at the negative electrode and are redeposited as metallic zinc, and the nickel compound at the positive electrode is oxidized. Electrons flow through the external circuit to form an electric current to supply power to the load.

[0003] Nickel-zinc batteries use an alkaline electrolyte (commonly potassium hydroxide solution). In such an electrolyte environment, the zinc negative electrode has a strong reducing property due to its relatively negative electrode potential. Zinc is chemically active in the alkaline electrolyte and naturally has a tendency to corrode, which is called zinc corrosion. Its corrosion process mainly occurs through reaction with hydroxide ions in the electrolyte. This corrosion reaction continuously occurs during the charge-discharge cycle of the battery, and as the operating temperature of the battery increases, the corrosion rate increases exponentially; the rapid zinc corrosion causes continuous loss of the active material of the zinc negative electrode, resulting in rapid attenuation of the battery capacity. At the same time, the uneven substances generated by corrosion deposit on the electrode surface, changing the microstructure of the electrode, hindering ion transport and electron conduction, reducing the high-temperature stability of the battery, and reducing the cycle life.

[0004] When the electrode potential is lower than the equilibrium potential of the hydrogen electrode, hydrogen ions in the electrolyte can obtain electrons to undergo a reduction reaction to generate hydrogen gas, which is called the hydrogen evolution reaction. The reaction not only consumes the battery power in vain, resulting in a reduction in the energy efficiency of the battery and a reduction in the cycle life of the battery; but also the generated hydrogen gas will accumulate inside the battery, increasing the internal pressure of the battery, damaging the battery sealing structure, and even causing safety hazards such as battery swelling and explosion in severe cases. Summary of the Invention

[0005] Aiming at the problems that the existing nickel-zinc batteries have reduced high-temperature stability and cycle life due to the hydrogen evolution reaction or zinc corrosion, the present application provides an electrolyte for nickel-zinc batteries and a nickel-zinc battery using the same.

[0006] In a first aspect, the present invention provides an electrolyte for a nickel-zinc battery, including a first additive and a second additive. The first additive includes borate, and the second additive includes at least one of fluoride salt and chloride salt.

[0007] Preferably, the borate includes one or two of ascharite and borax.

[0008] Preferably, in the electrolyte, the mass content of the borate is 1-2%.

[0009] Preferably, the fluoride salt includes one or more of sodium fluoride, potassium fluoride, lithium fluoride, and zinc fluoride; and / or, in the electrolyte, the mass content of the fluoride salt is 0.1-1%.

[0010] Preferably, the fluoride salt is selected from lithium fluoride.

[0011] Preferably, the chloride salt includes one or more of potassium chloride, sodium chloride, zinc chloride, and ammonium chloride; and / or, in the electrolyte, the mass content of the chloride salt is 0.1-1%.

[0012] Preferably, the chloride salt is selected from zinc chloride.

[0013] Preferably, the electrolyte further includes a third additive, the third additive includes a phosphate and an oxide, the phosphate includes one or more of disodium hydrogen phosphate, sodium dihydrogen phosphate, and dipotassium hydrogen phosphate; the oxide includes one or two of zinc oxide and magnesium oxide; In the electrolyte, the mass content of the phosphate is 1-2%, and the mass content of the oxide is 0.1-5%.

[0014] Preferably, the electrolyte further includes an electrolyte, the electrolyte includes an alkaline compound, and the alkaline compound includes one or more of KOH, NaOH, and LiOH; In the electrolyte, the mass content of the alkaline compound is 25-35%.

[0015] In a second aspect, the present application provides a nickel-zinc battery, including a positive electrode plate, a negative electrode plate, and an electrolyte, and the electrolyte is the electrolyte for a nickel-zinc battery described above.

[0016] For the electrolyte for a nickel-zinc battery provided by the present application, the first additive borate and the second additive chloride salt have a synergistic effect, and the synergistic effect is as follows: 1) Strengthen the complexation effect and control zinc deposition: The barrier effect of the borate strengthens the complexation effect of the chloride salt. By reducing the corrosion rate of zinc, zinc ions are released more slowly, and the complex formed by the chloride salt and zinc ions is more persistent. This synergistic effect effectively extends the action time of the chloride salt in the battery and makes the spontaneous deposition of zinc more controlled.

[0017] 2) Stable corrosion environment: In the electrolyte, the first additive borate can reduce the local pH value fluctuation, and the second additive chloride salt can stabilize the overall pH value of the electrolyte. The first additive and the second additive work synergistically to make the zinc corrosion environment more stable, reduce the generation of hydrogen and the spontaneous dissolution rate of zinc, and improve the battery safety performance.

[0018] 3) Prevent abnormal zinc deposition: The shielding effect of borate has the function of inhibiting the local dissolution of zinc, and the chloride salt can control the stable deposition of zinc ions and regulate the zinc ion concentration, which can effectively prevent the local excessive deposition of zinc, reduce the dendrite growth and electrode passivation problems, and improve the battery safety performance and cycle performance.

[0019] 4) Long-term protection of the zinc negative electrode: In the early stage of battery operation, borate plays a direct role in protecting the zinc electrode through a physical barrier, slowing down the spontaneous corrosion of zinc, while the chloride salt regulates the concentration and reaction rate of zinc ions chemically, further reducing the self-discharge rate; the two work together to provide long-term protection for the zinc negative electrode in the nickel-zinc battery, thus extending the battery cycle life, reducing the self-discharge rate, and improving the battery cycle performance.

[0020] The first additive borate provides physical isolation, reducing the corrosion and uneven deposition of zinc. The first additive borate and the second additive fluoride salt, through the synergistic effect of physical barrier and chemical protection, effectively slow down the self-discharge of the negative electrode of the nickel-zinc battery; the combination of the two provides long-term and stable protection for the battery, greatly improving the battery cycle performance and cycle life.

[0021] The electrolyte for nickel-zinc batteries provided by this application, the first additive can form a barrier structure at the zinc negative electrode interface. The first additive and the second additive work synergistically to enhance the stability of the zinc negative electrode interface, form a stable interface film at the negative electrode interface, and inhibit the occurrence of side reactions such as hydrogen evolution reaction or zinc corrosion, thereby extending the battery cycle life and improving the battery high-temperature performance and battery safety performance. Detailed implementation manners

[0022] In order to make the objectives, technical solutions and advantages of the present invention clearer and more understandable, the following further elaborates on the present invention in conjunction with embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0023] In order to illustrate the technical solutions of the present invention, the following will be described through specific embodiments.

[0024] In a first aspect, this application provides an electrolyte for nickel-zinc batteries, which includes a first additive and a second additive. The first additive includes borate, and the second additive includes at least one of fluoride salt and chloride salt.

[0025] In the electrolyte for nickel-zinc batteries, the first additive, borate, forms a barrier-like structure on the surface of the zinc electrode, which can inhibit the local dissolution of zinc. The borate directly protects the zinc electrode through a physical barrier, slowing down the spontaneous corrosion of zinc.

[0026] Zinc chloride controls the stable deposition of zinc ions (ion concentration regulation): This can effectively prevent the local excessive deposition of zinc, reducing dendrite growth and electrode passivation problems.

[0027] The second additive, chloride salt, complexes with zinc ions chemically, which can optimize the existing form and transport behavior of zinc ions in the electrolyte, control the stable deposition of zinc ions, play a role in regulating the zinc ion concentration, make the deposition and dissolution processes of zinc ions on the electrode surface more reversible, regulate the concentration and reaction rate of zinc ions, and further reduce the self-discharge rate. Specifically: During charging, the complexed zinc ions are more likely to uniformly accept electrons on the negative electrode surface and deposit into metallic zinc; during discharging, the zinc ions generated by the oxidation of metallic zinc can quickly form a complex with zinc chloride and enter the electrolyte, thereby improving the reversibility of the electrode reaction, reducing electrode polarization, and enhancing the charge-discharge efficiency and cycle performance of the battery.

[0028] For the electrolyte for nickel-zinc batteries provided by this application, the first additive, borate, and the second additive, chloride salt, have a synergistic effect, and the synergistic effect is as follows: 1) Strengthen the complexation and control zinc deposition: The barrier effect of borate strengthens the complexation effect of chloride salt. By reducing the corrosion rate of zinc, zinc ions are released more slowly, and the complex formed by chloride salt and zinc ions is more persistent. This synergistic effect effectively extends the action time of chloride salt in the battery and makes the spontaneous deposition of zinc more controllable.

[0029] 2) Stabilize the corrosion environment: In the electrolyte, the first additive, borate, can reduce local pH value fluctuations, and the second additive, chloride salt, can stabilize the overall pH value of the electrolyte. The first additive and the second additive work together to make the zinc corrosion environment more stable, reduce the generation of hydrogen and the rate of spontaneous dissolution of zinc, and improve the battery safety performance.

[0030] 3) Prevent abnormal zinc deposition: The shielding effect of borate can inhibit the local dissolution of zinc, and chloride salt can control the stable deposition of zinc ions and regulate the zinc ion concentration. This can effectively prevent the local excessive deposition of zinc, reduce dendrite growth and electrode passivation problems, and improve the battery safety performance and cycle performance.

[0031] 4) Long-term protection of the zinc anode: In the early stage of battery operation, borate acts directly to protect the zinc electrode through a physical barrier, slowing down the spontaneous corrosion of zinc, while chloride salt regulates the concentration and reaction rate of zinc ions chemically, further reducing the self-discharge rate; the combined action of the two provides long-term protection for the zinc anode in the nickel-zinc battery, thus extending the battery cycle life, reducing the self-discharge rate, and improving the battery cycling performance.

[0032] The fluoride salt in the second additive can form a stable interfacial film at the zinc anode interface, further inhibiting the hydrogen evolution side reaction and the spontaneous deposition of zinc ions at the zinc anode interface, and suppressing the formation of zinc dendrites.

[0033] The first additive borate provides physical isolation, reducing the corrosion and uneven deposition of zinc. The first additive borate and the second additive fluoride salt, through the synergistic effect of physical barrier and chemical protection, effectively slow down the self-discharge of the negative electrode of the nickel-zinc battery; the combination of the two provides long-term and stable protection for the battery, greatly improving the battery cycling performance and cycle life.

[0034] The electrolyte for the nickel-zinc battery provided by this application, the first additive can form a barrier structure at the zinc anode interface. The first additive and the second additive cooperate to enhance the stability of the zinc anode interface, form a stable interfacial film at the negative electrode interface, and inhibit the occurrence of side reactions such as hydrogen evolution reaction or zinc corrosion, thereby extending the battery cycle life and improving the battery high-temperature performance and battery safety performance.

[0035] In some embodiments, the borate includes one or two of szaibelyite and borax.

[0036] Specifically, the borate is selected from at least one of szaibelyite and borax, which can form a barrier-like structure on the surface of the zinc electrode, has the effect of inhibiting the local dissolution of zinc, and can directly protect the zinc electrode through a physical barrier, slowing down the spontaneous corrosion of zinc.

[0037] In some preferred embodiments, the borate is selected from szaibelyite.

[0038] The physical barrier structure formed by szaibelyite on the surface of the zinc anode is more stable, can better protect the zinc electrode, and further slows down the spontaneous corrosion of zinc.

[0039] In some implementations, in the electrolyte, the mass content of the borate is 1-2%.

[0040] Specifically, in the electrolyte, the mass content of the borate added is in the range of 1% to 2%. The content of the borate added can form a physical barrier on the surface of the zinc negative electrode, playing a role in protecting the zinc negative electrode, inhibiting the local dissolution of zinc, slowing down the spontaneous corrosion of zinc, and preferably inhibiting zinc corrosion. At the same time, it is beneficial to the synergistic effect of the borate and the second additive, improving the cycle performance and safety performance of the battery and extending the battery life.

[0041] In the electrolyte, the mass content of the borate can be 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, etc., as long as the mass content of the borate is within the range of 1% to 2%.

[0042] If the mass content of the borate is less than 1%, a physical barrier cannot be formed on the surface of the zinc negative electrode, and it cannot play a role in protecting the zinc negative electrode. If the mass content of the borate is higher than 2%, the content of the borate added is too high, and the barrier effect of the physical barrier is too high, affecting the charge and discharge of the battery.

[0043] In some embodiments, the fluoride salt includes one or more of sodium fluoride, potassium fluoride, lithium fluoride, and zinc fluoride.

[0044] Specifically, the fluoride salt includes one or more of sodium fluoride, potassium fluoride, lithium fluoride, and zinc fluoride, which is beneficial to forming a stable interfacial film at the zinc negative electrode interface, further inhibiting the hydrogen evolution side reaction and the spontaneous deposition of zinc ions at the zinc negative electrode interface, thereby inhibiting the formation of zinc dendrites, improving the cycle performance and safety performance of the battery, and extending the cycle life of the battery.

[0045] In some preferred embodiments, the fluoride salt is selected from potassium fluoride.

[0046] Specifically, the fluoride salt is selected from zinc fluoride, and the interfacial film formed at the negative electrode interface is complete, regular, and stable in structure, which can better inhibit the hydrogen evolution side reaction and the spontaneous deposition of zinc ions at the zinc negative electrode interface, and the cycle life and storage performance of the battery are better.

[0047] In some embodiments, in the electrolyte, the mass content of the fluoride salt is 0.1% to 1%.

[0048] Specifically, in the electrolyte, the mass content of the fluoride salt added is in the range of 0.1% to 1%, which is beneficial to forming a stable interfacial film of the fluoride salt at the zinc negative electrode interface, further inhibiting the hydrogen evolution side reaction and the spontaneous deposition of zinc ions at the zinc negative electrode interface, inhibiting the formation of zinc dendrites, and synergistically acting with the physical barrier formed by the first additive at the zinc negative electrode interface to improve the cycle performance and safety performance of the battery and extend the battery cycle life.

[0049] In the electrolyte, the addition amount of the fluorine salt can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, etc., as long as the mass content of the fluorine salt is within the range of 0.1 to 1%.

[0050] In the electrolyte, if the content of the fluorine salt is lower than 0.1%, the content of the fluorine salt contained is too low to form an interfacial film at the zinc negative electrode interface; if the content of the fluorine salt is higher than 1%, the thickness of the interfacial film formed at the zinc negative electrode interface is too high, which affects the charge and discharge performance of the battery and the cycle performance of the battery.

[0051] In some embodiments, the chloride salt includes one or more of potassium chloride, sodium chloride, zinc chloride, and ammonium chloride.

[0052] Specifically, the chloride salt includes one or more of potassium chloride, sodium chloride, zinc chloride, and ammonium chloride. The chloride salt is selected from the above types, which is beneficial for the chloride salt to complex with zinc ions chemically, can optimize the existing form and transport behavior of zinc ions in the electrolyte, control the stable deposition of zinc ions, play a role in regulating the concentration of zinc ions, make the deposition and dissolution processes of zinc ions on the electrode surface more reversible, play a role in regulating the concentration and reaction rate of zinc ions, and further reduce the self-discharge rate.

[0053] In some embodiments, in the electrolyte, the mass content of the chloride salt is 0.1 to 1%.

[0054] Specifically, in the electrolyte, when the mass content of the chloride salt is within the range of 0.1 to 1%, it is beneficial for the chloride salt to cooperate with the first additive, strengthen the complexation of the chloride salt with zinc ions and control zinc deposition, stabilize the corrosion environment, prevent abnormal zinc deposition, protect the zinc negative electrode for a long time, improve the cycle performance and safety performance of the battery, and extend the cycle life of the battery.

[0055] In the electrolyte, the mass content of the chloride salt can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, etc., as long as the mass content of the chloride salt is within the range of 0.1 to 1%.

[0056] In the electrolyte, if the mass content of the chloride salt is lower than 0.1%, the content of the chloride salt contained in the electrolyte is low, there is less chloride salt complexed with zinc ions, it cannot control zinc deposition well, cannot effectively protect the zinc negative electrode, cannot inhibit the hydrogen evolution reaction or zinc corrosion, and cannot effectively improve the battery performance. If the mass content of the chloride salt in the electrolyte is higher than 1%, it cannot effectively stabilize the pH value of the electrolyte, cannot effectively inhibit the hydrogen evolution reaction, the content of the chloride salt is relatively high, it complexes with more zinc ions, affects the normal charge and discharge of the battery, cannot effectively control zinc deposition, and affects the high-temperature performance of the battery.

[0057] In some preferred embodiments, the chloride salt is selected from zinc chloride.

[0058] The chloride salt being selected from zinc chloride is more conducive to synergizing with the first additive, resulting in better cycle performance and safety performance of the battery and extending the cycle life of the battery.

[0059] In some embodiments, the electrolyte further includes a third additive, the third additive includes phosphate, and the phosphate includes one or more of disodium hydrogen phosphate, sodium dihydrogen phosphate, dipotassium hydrogen phosphate.

[0060] Specifically, adding phosphate to the electrolyte has the effect of buffering the pH value of the electrolyte; at the same time, phosphate can adsorb on the surface of the zinc negative electrode, changing the deposition behavior of zinc ions and making the zinc ion deposition more uniform; phosphate can also form a protective film on the surface of the zinc electrode to prevent direct contact between ions such as hydroxide ions in the electrolyte and the zinc negative electrode, reducing zinc corrosion.

[0061] In some embodiments, in the electrolyte, the mass content of the phosphate is 1-2%.

[0062] In the electrolyte, when the mass content of phosphate is in the range of 1-2%, it is beneficial to maintain the stability of the electrolyte pH value and improve the performance of the zinc electrode, thereby enhancing the cycle stability of the battery. If the mass content of phosphate is less than 1%, it cannot effectively maintain the pH value of the electrolyte and cannot play a good buffering role; at the same time, a stable protective film cannot be formed on the surface of the zinc negative electrode, affecting the cycle stability of the battery. If the mass content of phosphate is higher than 2%, there is more phosphate, and the thickness of the protective film formed on the surface of the zinc negative electrode is too high, increasing the internal resistance of the battery.

[0063] The mass content of phosphate in the electrolyte can be 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, etc., as long as the mass content of phosphate is within the range of 1-2%.

[0064] In some embodiments, the third additive further includes an oxide, and the oxide includes one or two of zinc oxide and magnesium oxide.

[0065] Specifically, zinc oxide and magnesium oxide can adsorb some impurity ions in the electrolyte to prevent these impurity ions from triggering unnecessary side reactions; at the same time, they can also reduce the chemical reaction activity between the zinc electrode and the electrolyte, reducing the occurrence of side reactions such as hydrogen evolution. The inhibition of side reactions by the oxide helps to improve the safety and cycle performance of the battery. The oxide includes one or two of zinc oxide and magnesium oxide, and the oxide can form a synergistic effect with negative electrode active materials such as zinc powder, improving the utilization rate of the negative electrode active materials and improving the battery capacity.

[0066] In some embodiments, in the electrolyte, the mass content of the oxide is 0.1% to 5%.

[0067] Specifically, in the electrolyte, when the mass content of the oxide is in the range of 0.1% to 5%, the side reactions of the battery are reduced, the hydrogen evolution reaction is reduced, the utilization rate of the negative active material is improved, the cycle capacity of the battery is increased, and the safety performance of the battery is improved.

[0068] In the electrolyte, the mass content of the oxide can be 0.1%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, etc., as long as the mass content of the oxide is within the range of 0.1% to 5%.

[0069] In some embodiments, the electrolyte further includes an electrolyte, the electrolyte includes an alkaline compound, and the alkaline compound includes one or more of KOH, NaOH, and LiOH; In the electrolyte, the mass content of the alkaline compound is 25% to 35%.

[0070] Specifically, the electrolyte includes an alkaline compound. The alkaline compound is selected from the above types and the above mass content range. The alkaline compound can ionize hydroxide ions, provide good ionic conductivity for the electrolyte, reduce the internal resistance of the battery, and improve the performance of the battery. If the mass content of the alkaline compound is too low, the ionic conductivity of the electrolyte decreases and the internal resistance of the battery increases. If the mass content of the alkaline compound is too high, the viscosity of the electrolyte increases, which is not conducive to the transmission of zinc ions, accelerates side reactions such as the corrosion of the zinc negative electrode, affects the cycle performance of the battery, and reduces the cycle life of the battery.

[0071] In the electrolyte, the mass content of the alkaline compound can be 25%, 27%, 28%, 29%, 30%, 32%, 33%, 35%, etc., as long as the mass content of the alkaline compound is within the range of 25% to 35%.

[0072] The electrolyte further includes a solvent, and the solvent is water.

[0073] In a second aspect, the present application provides a nickel-zinc battery, including a positive electrode sheet, a negative electrode sheet, and an electrolyte, and the electrolyte is the electrolyte for the nickel-zinc battery described above.

[0074] The nickel-zinc battery provided by the present application, using the electrolyte provided by the present application, can form a stable interfacial film at the negative electrode interface, enhance the stability of the zinc negative electrode interface, inhibit the occurrence of side reactions such as hydrogen evolution reaction or zinc corrosion, extend the cycle life of the battery, and improve the high-temperature performance and safety performance of the battery.

[0075] The nickel-zinc battery of the present application can be applied to electrical equipment, which can be a smart lock, a power tool, a lamp or a toy. Since the nickel-zinc battery of the electrical equipment has a longer service life and storage performance, the performance of the electrical equipment can be improved.

[0076] The positive electrode plate and the negative electrode plate in the nickel-zinc battery are prior art.

[0077] For example, the positive electrode plate includes a positive electrode current collector and a positive electrode coating covering the surface of the positive electrode current collector. The positive electrode coating includes a positive electrode active material, a positive electrode additive, and a positive electrode binder. Regarding the mixing ratio among the positive electrode active material, the positive electrode additive, and the positive electrode binder, the present application does not make any limitation and can refer to the prior art.

[0078] The positive electrode active material includes Ni(OH)2, and the positive electrode additives include ZnO, CoO, Ni powder, Ca(OH)2, Y2O3, Yb2O3, graphite, etc.

[0079] The positive electrode binder includes CMC, PTFE, etc.

[0080] The negative electrode plate includes a negative electrode current collector and a negative electrode coating provided on the surface of the negative electrode current collector.

[0081] The negative electrode coating includes a negative electrode active material, an inorganic oxide additive, an organic additive, a surfactant, and a negative electrode binder. Regarding the negative electrode active material, the negative electrode additive, the conductive agent, the thickening agent, the dispersant, and the negative electrode binder; their mixing ratios are not limited in the present application and can refer to the prior art.

[0082] The negative electrode active material includes zinc and zinc oxides.

[0083] The negative electrode additives include In2O3, Bi2O3, Al2O3, etc.

[0084] The thickening agent includes one or more of sodium carboxymethyl cellulose, hydroxyethyl cellulose, and hydroxypropyl methyl cellulose.

[0085] The conductive agent includes one or more of activated carbon, conductive carbon black, carbon nanotubes, graphene, and vapor grown carbon fibers.

[0086] The dispersant includes one or more of sodium polyacrylate, potassium polyacrylate, and polyacrylamide.

[0087] The negative electrode binder includes one or more of styrene-butadiene rubber and polytetrafluoroethylene.

[0088] Example 1 This example is used to illustrate a nickel-zinc battery electrolyte and a nickel-zinc battery disclosed by the present invention, and includes the following operation steps: 1) Preparation of the positive electrode: The following substances are stirred evenly according to the mass ratio of 85% Ni(OH)2, 1 wt% ZnO, 3 wt% CoO, 2 wt% Ni powder, 2 wt% Ca(OH)2, 2 wt% Y2O3, 1 wt% Yb2O3, 3 wt% graphite, 0.5 wt% CMC, and 0.5 wt% PTFE, and then coated on the positive current collector. After rolling, softening, and cutting, the positive electrode of the nickel-zinc battery is obtained.

[0089] 2) Preparation of the negative electrode: (1) Take 1.5 wt% conductive carbon black as the conductive substance, 0.32 wt% sodium carboxymethyl cellulose as the thickener, and 1.5 wt% sodium polyacrylate as the dispersant. After mixing evenly, add 0.05 wt% In2O3, 2.8 wt% Bi2O3, and 4 wt% Al2O3, stir for 30 min, then add 1.5 wt% Ca(OH)2 and stir for 30 min. After mixing evenly, add 61 wt% ZnO and 27 wt% Zn in three portions, mix evenly again, and finally add 0.33 wt% binder and mix again to obtain the negative electrode slurry. (2) Coat the negative electrode slurry on the inclined drawn tin-coated copper mesh current collector, and obtain the negative electrode of the nickel-zinc battery after rolling, softening, and cutting.

[0090] 3) Preparation of the electrolyte: The first additive in the electrolyte is selected from ascharite, and the second additive is selected from zinc chloride.

[0091] The composition of the electrolyte in this example is 24 wt% KOH, 3 wt% NaOH, 1 wt% LiOH, 1 wt% disodium hydrogen phosphate, 1 wt% ascharite, 1 wt% zinc oxide, 0.5 wt% zinc chloride, and the rest is water.

[0092] 4) Preparation of the nickel-zinc battery: Stack the positive electrode, separator, and negative electrode in sequence, with the separator in the middle of the positive and negative electrodes to prepare the battery core. Place the battery core in the outer packaging bag for drying, inject the above electrolyte, and obtain the nickel-zinc battery through processes such as vacuum packaging, standing, forming, and shaping.

[0093] Examples 2 - 21 and Comparative Examples 1 - 4 Examples 2 - 21 are mostly the same as Example 1, except that the types and contents of the first additive and the second additive in the electrolyte are different. See Table 1 for details, and the rest is the same as Example 1.

[0094] Comparative Examples 1 - 4 are mostly the same as Example 1, except that the types and contents of the first additive and the second additive in the electrolyte are different. See Table 1 for details, and the rest is the same as Example 1.

[0095] Table 1 Performance testing Perform the following performance tests on the above examples and comparative examples.

[0096] Cycle life At a temperature of 25 °C, the zinc-nickel batteries prepared in each example and comparative example were charged at 1C to 1.9V and then charged at a constant voltage of 1.9V until the cut-off current was 13.5 mA, and discharged at 1C to 1.3V. The charge and discharge were repeated until the battery capacity was reduced to 60% of the first charge, and the number of charge and discharge cycles was recorded. High-temperature storage performance (1) Under the condition of 25 °C, the battery was fully charged by a constant current and constant voltage charging method, charged at 0.2C to 1.9V, and then charged at a constant voltage of 1.9V until the cut-off current was 13.5 mA to end the charging.

[0097] (2) The fully charged battery was placed in an oven at 60 °C and stored for 28 days.

[0098] (3) After the storage, it was discharged at 0.2C to 1.3V, then charged using the same charging method as in (1), left standing for 10 min, and then discharged at 0.2C to 1.3V. The above charging and discharging steps were repeated 3 times.

[0099] The above test results are shown in Table 2 Table 2 It can be seen from Tables 1 and 2 that when comparing Example 1 with Comparative Example 1, there are no first additive and second additive in Comparative Example 1, and the battery has a low cycle life and poor high-temperature storage performance; when comparing Example 1 with Comparative Example 2, only the first additive, serpentine, is added in Comparative Example 2, but the battery has poor high-temperature storage performance and normal-temperature cycle performance; when comparing Example 1 with Comparative Examples 3 and 4, only chloride salt or fluoride salt is added to the electrolyte, and the storage performance and cycle performance of the battery are still poor; it shows that adding the first additive and the second additive to the electrolyte of the nickel-zinc battery, the first additive can form a barrier structure at the zinc negative electrode interface, and the first additive and the second additive cooperate to enhance the stability of the zinc negative electrode interface, form a stable interface film at the negative electrode interface, and inhibit the occurrence of side reactions such as hydrogen evolution reaction or zinc corrosion, thereby prolonging the cycle life of the battery and improving the high-temperature performance and safety performance of the battery.

[0100] Comparing Example 1, Examples 4-5, Example 8 with Examples 6 and 7, the content of borate in Example 6 is less than 1%, which cannot form an effective physical barrier on the surface of the zinc negative electrode, resulting in spontaneous corrosion of zinc, and poor storage performance and cycling performance of the battery; the content of borate in Example 7 is higher than 2%, and the physical barrier has a relatively high barrier effect, which affects the charge and discharge of the battery, and the cycling performance of the battery is poor; it shows that when the content of borate in the electrolyte is in the range of 1% to 2%, the added borate content in the battery can form a physical barrier on the surface of the zinc negative electrode, play a role in protecting the zinc negative electrode, inhibit the local dissolution of zinc, slow down the spontaneous corrosion of zinc, and preferably inhibit zinc corrosion; at the same time, it is beneficial to the synergistic effect of borate and the second additive, improving the cycle life, high-temperature storage performance and safety performance of the battery.

[0101] Comparing Examples 1-3, when both chloride salt and fluoride salt are added to the electrolyte, the obtained battery has a higher cycle life, a high high-temperature storage capacity retention rate, and a higher capacity recovery rate. Comparing Example 1, Examples 10-11 with Examples 12-13, when the content of zinc chloride added to the electrolyte is less than 0.1%, the complexation effect between the chloride salt and zinc ions is weak, and the irregular deposition of zinc cannot be inhibited, resulting in poor cycle life of the battery and low high-temperature storage capacity retention rate. When the content of zinc chloride is higher than 1%, the complexation effect between the chloride salt and zinc ions is enhanced, and the deposition rate of zinc is weakened, increasing the cycle life of the battery, but the high-temperature storage performance of the battery is still poor; it shows that when the content of the second additive chloride salt added to the electrolyte is in the range of 0.1 to 1%, the obtained battery has a high cycle life and good high-temperature storage performance. Comparing Examples 16, 18-19 with Examples 20-21 shows that when the content of the second additive fluoride salt added to the electrolyte is in the range of 0.1 to 1%, the obtained battery has a high cycle life and good high-temperature storage performance.

[0102] Comparing Example 1 with Examples 14-15 shows that the types of chloride salts added to the electrolyte include one or more of potassium chloride, sodium chloride, zinc chloride, and ammonium chloride, all of which have the effect of improving the cycle life and high-temperature storage performance of the battery. Comparing Example 2 with Examples 16 and 17 shows that the types of fluoride salts added to the electrolyte include one or more of sodium fluoride, potassium fluoride, lithium fluoride, and zinc fluoride, all of which have the effect of improving the cycle life and high-temperature storage performance of the battery.

[0103] The above examples are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing examples, those of ordinary skill in the art should understand that they can still modify the technical solutions described in the foregoing examples, or perform equivalent replacements for some of the technical features. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present invention, and should all be included within the protection scope of the present invention.

Claims

1. An electrolyte for a nickel-zinc battery, characterized in that, It includes a first additive and a second additive. The first additive includes borate, and the second additive includes at least one of fluoride salt and chloride salt.

2. The electrolyte for a nickel-zinc battery according to claim 1, characterized in that, The borate includes one or both of szaibelyite and borax.

3. The electrolyte for a nickel-zinc battery according to claim 1 or 2, characterized in that, In the electrolyte, the mass content of the borate is 1-2%.

4. The electrolyte for a nickel-zinc battery according to claim 1, wherein, The fluoride salt includes one or more of sodium fluoride, potassium fluoride, lithium fluoride, and zinc fluoride; and / or, in the electrolyte, the mass content of the fluoride salt is 0.1-1%.

5. The electrolyte for nickel-zinc batteries according to claim 4, characterized in that, The fluoride salt is selected from lithium fluoride.

6. The electrolyte for a nickel-zinc battery according to claim 1, wherein The chloride salt includes one or more of potassium chloride, sodium chloride, zinc chloride, and ammonium chloride; and / or, in the electrolyte, the mass content of the chloride salt is 0.1-1%.

7. The electrolyte for nickel-zinc batteries according to claim 6, characterized in that, The chloride salt is selected from zinc chloride.

8. The electrolyte for a nickel-zinc battery according to claim 1, wherein The electrolyte further includes a third additive, and the third additive includes phosphate and oxide. The phosphate includes one or more of disodium hydrogen phosphate, sodium dihydrogen phosphate, and dipotassium hydrogen phosphate; The oxide includes one or both of zinc oxide and magnesium oxide; In the electrolyte, the mass content of the phosphate is 1-2%, and the mass content of the oxide is 0.1-5%.

9. The electrolyte for nickel-zinc batteries according to claim 1, wherein The electrolyte further includes an electrolyte, and the electrolyte includes an alkaline compound. The alkaline compound includes one or more of KOH, NaOH, and LiOH; In the electrolyte, the mass content of the alkaline compound is 25-35%.

10. A nickel-zinc battery, characterized in that, It includes a positive electrode plate, a negative electrode plate, and an electrolyte. The electrolyte is the electrolyte for a nickel-zinc battery according to any one of claims 1-9.

Citation Information

Cited By

  • Zinc oxide negative electrode material, preparation method thereof and nickel-zinc battery

    CN122393197A